Visualization and semi-quantitative analysis of dissolution processes at artificial structures in carbonate rocks using optical, 3D micro-scanning and confocal laser scanning microscopy - Annette Dietmaier; Justin Mattheis; Daniel Weller; Ingrid Stober; Michael Drews; Thomas Baumann (Geothermal Energy)
Abstract The Northern Alpine Foreland Basin in southeast Germany hosts more deep geothermal plants than any other region in the country. Its primary aquifer, the Upper Jurassic, is composed of permeable carbonates containing water with temperatures exceeding $$150\,^{° }$$ 150 ∘ C in the southern margin and low total dissolved solids ( $$\le$$ ≤ 2 g/L) at depths of up to 4000 m. Its sustainable use of geothermal energy depends on an efficient exploitation strategy concerning the entire reservoir, which is influenced by the development of flow paths between production and reinjection wells. The Upper Jurassic’s waters show a carbonate signature with calcium and magnesium often replaced by sodium due to ion exchange along the infiltration pathways. These waters become undersaturated upon cooling, and dissolution around reinjection wells has been previously documented. Assessing short- to medium-term localized dissolution experimentally is challenging. While dissolution kinetics and overall volume changes have been studied in the field, microscopic changes to flow paths remain less under investigation. This study used a time-lapse experiment to evaluate microscopic changes during dissolution in limestone samples exposed to elevated $$\text {CO}_{2}$$ CO 2 partial pressure in an autoclave. For an effective observation, we used artificial structures to localize the dissolution effects. Post-treatment analysis included Raman microscopy, 3D micro-scanning, confocal laser scanning microscopy (CLSM), and optical microscopy with image stacking, with a strong focus on the latter three. Each imaging method had distinct strengths and limitations. CLSM provided high-resolution surface roughness assessments but could not capture areas beneath overhangs. Optical microscopy is affordable and user-friendly and was effective for visualizing preferential dissolution pathways but lacked precise roughness information. 3D micro-scanning, despite lower resolution, uniquely resolved overhangs. The dissolution processes led to significant surface roughening, forming micrometer-scale moldic pores and preferential pathways. Artificial structures widened and deformed, with 3D micro-scanning quantifying these changes effectively and CLSM revealing fine-scale roughness details. Increased fracture surface roughness and widening of flow paths enhance water transport and dissolution, potentially accelerating thermal breakthroughs at geothermal plants. Understanding these processes is essential for predicting reservoir behavior, improving geothermal energy extraction efficiency, and exploiting aquifers sustainably.